Aleitamento materno e aspectos emocionais durante o período pandêmico do COVID 19 em dois municípios da região metropolitana de Belém-Pa-Brasil - SILVA, Paula Rayssa Lobato da (2023)
Introduction: The monitoring of women and guidance on the benefits of breast milk are of paramount importance for the mother to choose to breastfeed. It is necessary that the approach is effective and gradual so that she feels pleasure and well-being when practicing the act of breastfeeding. This activity is vulnerable to interference from multiple factors that encompass maternal principles, especially with regard to the conduct of each woman in these circumstances. Maternal insecurity was one of the factors that puerperal women reported presenting and influencing early weaning, since this insecurity may be related to the production of breast milk. Therefore, the present research aimed to describe which emotional aspects were reported by women who breastfed during the pandemic period in two municipalities in the metropolitan region of Belém. Methodology: Quantitative, descriptive and cross-sectional study with the application of an online questionnaire via Google forms. Conclusion: The research results reflect on the importance of investigating factors related to the emotional aspect of women during pregnancy and postpartum periods, in order to prevent and treat these changes or disorders, as they influence maternal health and consequently in the practice of breastfeeding. However, it is important that new research be developed to help health professionals in encouraging this practice that saves so many lives.